Composition of Essential Oil Isolated From Marigold (Tagetes Erecta L.) Flowers Cultivated in Lahore, Pakistan (Bangladesh Journal of Botany, 2022)
The composition of essential oil of marigold (Tagetes erecta L.) flowers was investigated. The oil was analyzed by GC-MS for identification of various components. Among these, 3-cyclohexene-1-methanol, α, α,4-trimethyl-, acetate was the most abundant compound (31.67%) followed by phenol, 2,4-bis (1,1- dimethylethyl)- (14.35%) and eucalyptol (14.27%). Other compounds included dodecanoic acid (5.97%), tetradecanoic acid (5.58%), octadecane (4.93%), propanoic acid, 2-bromo-2-methyl-, ethyl ester (5.43%), cyclohexanol, 1-methyl-4-(1-methylethanyl)-, acetate (5.33), n-hexadecanoic acid (4.70), p-menth-1-en-8-ol (4.20%) and thymol (3.57%).Bangladesh J. Bot. 51(4): 683-688, 2022 (December)